ответ
Пошаговое объяснение:1. 4x=24+x; 3x=24; x=8
2. 8x-8=20-6x
8x+6x=20+8
14x=28
X=2
3.4(x-3)=x+6
4x-12=x+6
4x-x=6+12
3x=18
X=6
4. 3(1-x)=1-4x+5x+10
-3x+4x-5x=10-3+1
-4x=8
X=-2
1. 4x=24+x
3x=24
x=8
ответ
Пошаговое объяснение:1. 4x=24+x; 3x=24; x=8
2. 8x-8=20-6x
8x+6x=20+8
14x=28
X=2
3.4(x-3)=x+6
4x-12=x+6
4x-x=6+12
3x=18
X=6
4. 3(1-x)=1-4x+5x+10
-3x+4x-5x=10-3+1
-4x=8
X=-2
1. 4x=24+x
3x=24
x=8
2. 8x-8=20-6x
8x+6x=20+8
14x=28
X=2
3.4(x-3)=x+6
4x-12=x+6
4x-x=6+12
3x=18
X=6
4. 3(1-x)=1-4x+5x+10
-3x+4x-5x=10-3+1
-4x=8
X=-2